The Dynamic Interaction Between Film Narration and Literary Field: Taking Chen Kaige’s “The Legend of the Demon Cat” as an Instance - Zhang, Shuning (Journal of language teaching and research, 2025)
The film “The Legend of the Demon Cat” is an adaptation of the Japanese novel “The Grand Tang Dynasty Ghost Banquet of Konghai the Monk”. It represents another fantastical-themed creation by Chen Kaige following “The Promise”. With its sumptuous and dazzling scenes and elaborate plot arrangements, it not only recreates the opulent ambiance of the Tang Dynasty but also permeates classical literary connotations throughout the details, achieving an organic fusion of film and literature. Generally, the lens narration of “The Legend of the Demon Cat” is intertwined with Chen Kaige’s literary construction of “poeticizing” the film. Whether it is the literary manifestation of shooting techniques, the three-dimensional portrayal of literati figures, or the visual presentation of literary undertones, all of these exemplify the complementarity between literary art and film art. This literarization of films and the infiltration of literature into film and television have, to a certain extent, enriched the aesthetic palette of domestic films and furnished certain shooting references for future films adapted from fantasy literature.